Efectos de la demanda interna y choques externos en la inflación en el Perú: periodo 2003:01 al 2023:09 - Valera Torres, Britney Cristina (2025)
The study quantifies whether domestic demand or external shocks drive inflationary fluctuations for both normal and exceptional periods (without and with government intervention) during the period 2003:01 to 2023:09. In addition, it reviews the effects of the variation in the monetary policy rate on inflation and productive activity through simultaneous dynamic relationships. The study hypotheses affirm that domestic demand contributes in greater proportion to the increase in general and core inflation in normal periods and external shocks to both inflations to a greater extent during exceptional periods. Likewise, the increase in the policy rate decreases inflation and productive activity. Multiple regression with instrumental variables is used to correct the simultaneity between inflation and variation in the nominal exchange rate and the use of dichotomous variables to isolate normal and exceptional periods. For the dynamic relationships, a vector autoregressive (VAR) model is used that shows the shocks of innovations and the simultaneous responses to the impulse between the study variables. The findings show that the contribution of domestic demand to headline and core inflation in normal periods is on average 56% and 52%. The effect of external shocks on headline and core inflation in exceptional periods is 79% and 54%. Monetary tightening has an effect of around 2 years to bring inflation close to zero. The cost to productive activity impacts after 12 months with slight recessions in the following 12 months.